Index based on atmospheric pressures for the detection of El Niño Southern Oscillation effects off the Peruvian coast - Quispe, Carlos (2008)
The behavior of an index based on the difference of atmospheric pressure between Darwin and Paita (IDP) was analyzed, as an indicator of the effects of El Niño and La Niña in the Northern Humboldt Current Ecosystem (NHCE). The temporal variation of IDP at monthly scale had a good correlation with the Southern Oscillation Index (SOI). Additionally, the maximum cross correlation between IDP and AN3.4 was found at a lag of -3, which could allow to use the IDP to simulate the AN3.4. The behavior of IDP obeys to the complex interaction between the atmospheric system of the region and the Equatorial Pacific.